“Bung Karno” School in the Perspective of Islam in the Archipelago - YASIN, Nur Ali; YAQIN, Mohammad Nurul (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:This study aims to examine the controversy surrounding the statement of